Control of deposits on pipeline systems by the method of free oscillations - E. V. Garnyshova; E. V. Izmaylova (Известия высших учебных заведений: Проблемы энергетики)
RELEVANCE. There are a large number of heat exchangers in operation enterprises that operate under various temperature conditions. Steam, hot water, heated products of oil refining and other industries, which may contain oxides of iron, aluminum, calcium sulfate silicates, etc., are used as a heating agent. The efficiency of the heat exchange equipment depends on the condition of the heating surfaces. Contamination of these surfaces with various deposits dramatically reduces the heat transfer coefficient, which leads to a significant increase in heat consumption. The nature of the deposits depends on the properties of the heating agent and the heated medium.THE PURPOSE. The purpose is to assess the possibility of controlling deposits on the surfaces of heat exchange equipment by the free oscillation method. The presence of deposits changes the mass of structures and, consequently, the natural frequencies of vibrations, the analysis of which can determine not only the presence and thickness of deposits, as well as their appearance.METHODS. The paper shows the results of experimental studies conducted using a hardware and software package and calculations of natural vibrations of the surfaces of heat exchange equipment in the ANSYS software package to identify their dependence on the thickness and density of deposits. A plate, a pipe, and a pressurized pipe were modeled as heat transfer surfaces.RESULTS. The results obtained experimentally and computationally coincided, and it was concluded that the free oscillation method makes it possible to determine not only the presence of deposits on heat exchange surfaces, but their thickness and appearance.CONCLUSION. The free oscillation method can detect deposits in a timely manner and monitor their condition, which in turn will, reduce overall operating costs, increase energy efficiency and extend service life.